Pemanfaatan Digital Content Tiktok dan Buku Kas Berbasis Android Bagi UMKM Anggota CU Hatirongga - Liharman Saragih; Wico Jontarudi Tarigan; Muhammad Kevin Jhody Saragih (Universitas, 2022)
Micro, Small and Medium Enterprises (MSMEs) face obstacles in financial reporting according to standards, do not know how much pure profit is obtained, lack of understanding of basic knowledge of financial records, lack of understanding of Android-based financial applications, and difficulty in obtaining financing from institutions. The purpose of this community service is to increase understanding of Tiktok Digital Content knowledge in business development and the ability to compile an Android - based cash book. Community service involves MSME actors who are members of the CU Hatirongga Pematangsiantar cooperative as objects of assistance and training. The method used in the training is an online method, indirect face – to - face and mentoring, namely by analyzing and problem solving. Materials for making tiktok accounts and android-based cash books are presented with lectures, training, questions and answers, demonstrations, and online case resolution. The material is made in a simple and attractive way so that the content of tiktok and android-based cashbooks can be understood by MSMEs, members of the CU Hatirongga Pematangsiantar cooperative. Furthermore, the recording process begins with examples of simple transactions that are usually carried out through the SI APIK application, an android application issued by Bank Indonesia. The results of the training and assistance in the creation of tiktok content and cashbooks through this android-based application are expected to run well